PENGGUNAAN MEDIA AUDIO UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK CERITA RAKYAT PADA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SD NEGERI LENGKONG - Maryanti, Ika; Mukhidin, Mukhidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2017)
This study aims to determine the improvement of listening ability in grade V students in Lengkong State Elementary School using audio media. The type of research used is a case study with Classroom Action Research (collaborative Classroom Action). The form of collaborative classroom action research with colleagues as observers. The subject of this research is the students of grade V of State Elementary School Lengkong which amounted to 18 people. The object of this research is the ability to listen to folklore. The research design used was Kemmis and Mc.Taggart. Data collection methods used in this study are: 1) test, 2) observation, and 3) field notes. Data analysis technique is done descriptively qualitative. The results showed that learning to listen to folklore using audio media can improve the ability of listening to folklore. Based on the results of the pretest cycle 1 students on average get the score of listening ability to students in the first cycle, the students get an average score of 50, then on cycle II score The average class increased to 87.5, this shows there is an increase in listening ability in grade V students on the material Responding to events that occur around orally.